PENGARUH ULTRASOUND DIATHERMY DAN OPEN KINETIC CHAIN EXERCISE TERHADAP KEMAMPUAN FUNGSIONAL PADA PENDERITA OSTEOARTHRITIS GENU - Kristiani Hariskawati; Sartoyo Sartoyo; Yohanes Deo Fau; Fransisca Xaveria Hargiani (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: Osteoarthritis is one of the joint disorders that has decreased joint function, resulting in decreased functional ability in daily activities. Physiotherapy treatment to reduce complaints felt by giving ultrasound diathermy and open kinetic chain exercises. The purpose of this study was to determine the effect of ultrasound diathermy and open kinetic chain exercises in improving functional ability in patients with osteoarthritis genu. Methods: This study used pre-experimental methods in a one-group pretest-posttest design. Functional ability was measured using the knee injury and osteoarthritis outcome score (KOOS) scale before and after treatment, namely the administration of diathermic ultrasound and open kinetic chain exercises 2 times a week for 1 month, with a sample of 22 randomly selected respondents. Results: The paired sample t-test hypothesis showed a p-value = 0,000 (0,000<0,05). Conclusion: there is an effect of ultrasound diathermy and open kinetic chain exercise on improving functional ability in patients with osteoarthritis genu. Keywords: functional ability, open kinetic chain exercise, osteoarthritis genu, ultrasound diathermy